Gagasan Pelestarian Lingkungan dalam Antologi Merayakan Pohon di Kebun Puisi Karya Nyoman Wirata: Analisis Semiotik - Sri Puspitawati, Ni Putu (Humanis; Vol 20 No 1 (2017), 2017)
This research was conducted to analyzed “The Environmental Conservation Idea in the Anthology of Merayakan Pohon di Kebun Puisi by Nyoman Wirata”. Nyoman Wirata is a poet who cares about environmental preservation. His interest in environment is because of his profession as a teacher of environtment and art at one of SMP Negeri in Denpasar. This research discussed structure problem and expression of environmental conservation idea in the anthology of Merayakan Pohon di Kebun Puisi by Nyoman Wirata. Of the fifty-seven poems in this anthology, ten poems with the theme of environmental damage were selected by using the word “pohon” in each title. This research used literature review and analitical descriptive method of study. The theory used was structuralism and semiotic theories that focus on the study of signs used in literary works. These signs are interpreted to understand the idea of environmental preservation in the anthology of Merayakan Pohon di Kebun Puisi by Nyoman Wirata. Ten poems of Nyoman Wirata contain the idea of environmental conservation. This idea of environmental preservation was modified into figure of speech that describes the environment in a sadness situation.